Crisis management of tourism destinations - Beljić, Bojana (Hotel and Tourism Management, 2017)
It is an obvious fact that society is constantly changing. Simultaneously, the economy is changing too, and these changes also affect the sphere of tourism. A tourism destination must not only be aware of these changes happening at the environment, but also provide an adequate response to them. The concept of crisis as a deviation from the normal order of things, reflects on all three – a society, an economy and a tourism destination. Besides other happenings, the second half of XX and the beginning of XXI century will be remembered in the history of tourism as the period of dramatic changes. Tourism has become a worldwide phenomenon, an integral part of the life of the dominant world’s population. Undoubtedly, the tourism industry is one of the most sensitive and vulnerable industries in the time of crisis. Recent events which have had devastating consequences for tourism destinations range from natural disasters and epidemics, to terrorist attacks, making thus everlasting changes in the way in which tourism industry operates. Despite the general negative perception, a crisis does not necessarily lead to the collapse of a tourism destination.